Exploring Saudi College Students' Attitudes toward Using English Dictionaries at Albaha University - Elsadig Mohamed Khalifa (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The present paper addresses the attitudes of Saudi students toward using English dictionaries at Albaha University. A sample of 64 English majors in the College of Science and Arts in Almandaq took part in this study. A descriptive quantitative approach was implemented in this study. A 24-item questionnaire was applied in this study to collect the data. Data analysis was conducted using SPSS. Findings revealed that while most of the participants used bilingual dictionaries, few of them used monolingual dictionaries. Also, the findings showed that there was a lack of awareness among the students in using dictionary entries. Furthermore, a majority of students believe in the importance of using dictionaries for language learning. Integrating lexicography in the English course program is the main recommended implication to be taught. Teachers should implement activities related to dictionary skills in their English classes, such as using dictionary entries, including pronunciation, collocation, parts of speech, abbreviations, etc. Finally, students should be trained to use monolingual dictionaries in their language learning. These implications can be used to overcome the students’ difficulties in using dictionaries.